Kerusuhan Sosial: Kasus Pemilihan Kepala Desa Sirau Purbalingga = Social Riot: A Case of Village ead Election in Sirau Purbalingga. - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
The election of a village head is an example of democracy in the village society. However, it becomes a problem when the election of a village head does not follow the rule. This research study aims to explore what factors cause the riot and why it happens in the election of the village head.The result of the research shows that the social riot results the accumulation of disappointment due to the election result that does not match with people expectation. The disappointments include the lost of candidate they support, the misuse of committee authorities in doing their job so they are notneutral.Some factors that cause social riot can be classified into two, they are indirect and direct factors. The indirect causes are conflict in society caused by the misuse of Bangdes fund by the ex-village leader. The competition between the candidates in getting the voter is not fair, so abuses accur in the village head election. Moreover the committee of election is not neutral and not fair in doing their job. It is caused by the pressure of people who have some interests in the election. The direct causes of the social riot are the announcement of the vote calculation in which mass, know that the candidate they support lose and they are mobilized by botoh to make a social riot.When the social riot accured the security guard could not predict it so they could not handle the riot. As aconsequence, the riot spread to the whole village. To handle the riot, the security guard supported the police (Brimob) and TNI Batalyon 406 Purbalingga stop the riot.